PERANCANGAN PEMBUATAN DAN PENGUJIAN KINERJA CONTAINER N2 CAIR SEDERHANA UNTUK DEMONSTRASI SIFAT MEKANIK MATERIAL PADA SUHU RENDAH - Nur Aisyah, Rika
Liquid Nitrogen has been widely used in the field science and Industry. One of them is used in laboratory for impact testing purposes at low temperature. The test is usually carried out to observe the phenomenon of materials mechanical properties changes from ductile to brittle. Related to low temperature testing a portable container for liquid Nitrogen is requirred. Usually the liquid Nitrogen container is big, expensive, and non transportable. In this research a commercial low cost thermos has been chosen and became an alternative solution. The oustide wall of the thermos is made of aluminium that could easily transfer heat from surrounding. To increase heat insulation and to stabilise the container from easily tripped off a concrete is applied on the outer surface of the thermos. This is to retain the liquid nitrogen for at least 6 hours for a demonstration purposes to local high school which is easy to carry, cheap and using locally available materials. The concrete consist of cement, sand and water with 0.3 w/c water to cement ratio is casted to the outer wall. The liquid capacity of the thermos is 1.5 L. The method used for determining the remaining volume of liquid nitrogen were using theoritical calculation and direct measurement for 24 hours duration. In order to support the theoritical calculation, concrete conductivity has been determined i.e 0.667 W/m.K. The value is then used in the heat flow calculation for a period of time with 3.5, 2.5 and 1.5 cm concrete thicknesses. From calculation it is found that remaining liquid nitrogen volume on the thermos after 24 hours without a concrete layer is 251.53 ml whereas with 3.5 cm concrete is 251.84 ml. From 24 hours direct observation it is found that thermos without concrete layer has a remaining volume of 300 ml, whereas with 3.5 cm concrete is 450 ml. This has shown a significant 50% increase. In fact the remaining liquid nitrogen volume difference obtain by calculation and measurement which are 0.31 ml and 150 ml shown a very large discrepancy. Therefore the theoritical result should be recalculated in future research. Keywords: Liquid nitrogen, portable container, low cost commercially available thermos, heat conductivity and concrete insulator.